2019
DOI: 10.1371/journal.pone.0215550
|View full text |Cite
|
Sign up to set email alerts
|

Impact of malaria and hepatitis B co-infection on clinical and cytokine profiles among pregnant women

Abstract: Background The overlap of malaria and chronic hepatitis B (CHB) is common in endemic regions, however, it is not known if this co-infection could adversely influence clinical and immunological responses. This study investigated these interactions in pregnant women reporting to antenatal clinics in Ghana. Methods Clinical parameters (hemoglobin, liver function biomarker, peripheral malaria parasitemia, and hepatitis B viremia) and cytokine profiles were assayed and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…Though P. falciparum and HBV majorly trigger the release of the pro-inflammatory cytokines [16], the infections appeared not to markedly influence the inflammatory responses in the traders. It has been suggested that adults with P. falciparum infection show controlled inflammatory responses due to increased history of exposure, and that higher parasite loads are required to elicit the inflammatory responses and cause disease symptoms [33].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Though P. falciparum and HBV majorly trigger the release of the pro-inflammatory cytokines [16], the infections appeared not to markedly influence the inflammatory responses in the traders. It has been suggested that adults with P. falciparum infection show controlled inflammatory responses due to increased history of exposure, and that higher parasite loads are required to elicit the inflammatory responses and cause disease symptoms [33].…”
Section: Discussionmentioning
confidence: 87%
“…Also, it is common to find adults with chronic hepatitis B virus (HBV) infection who experience no disease symptoms [13]. Though current evidence shows no links between P. falciparum or HBV and CVDs [14,15], both pathogenic diseases majorly trigger inflammatory immune responses [16], and could exacerbate inflammatory responses in adults involved in chronic sedentary lifestyle, which may predispose them to hypertension and CVD.…”
Section: Introductionmentioning
confidence: 99%
“… 15 Overlapping HBV/malaria coinfection cases have been reported previously. 16 , 17 Both pathogens share an intrahepatic life cycle developmental stage, which may increase mortality and morbidity. 11 Nonetheless, whether HBV exerts an effect on the clinical presentation of malaria remains debatable.…”
Section: Discussionmentioning
confidence: 99%
“…While studies abound on epidemiology of single infection by P. falciparum and T. gondii, very few reports are available on co-infection of the two parasites. Meanwhile, several reports have associated malaria and toxoplasmosis with infections like hepatitis virus, HIV and helminths (Simpore et al, 2006;Ouermi et al, 2009;Cuadros et al, 2011;Morenikeji et al, 2016a,b;Jegede et al, 2017;Helegbe et al, 2018;Anabire et al, 2019). Only three countries in Sub-Saharan Africa had epidemiological data on co-infection of malaria and toxoplasmosis (Table 3).…”
Section: Concomitant Occurrence Of Malaria and Toxoplasmosis: The Knomentioning
confidence: 99%